Transient Receptor Potential Channels and Botulinum Neurotoxins in Chronic Pain - Go, Eun Jin; Ji, Jeongkyu; Kim, Yong Ho; Berta, Temugin; Park, Chul-Kyu (Frontiers in Molecular Neuroscience, 2021)
Pain afflicts more than 1.5 billion people worldwide, with hundreds of millions suffering from unrelieved chronic pain. Despite widespread recognition of the importance of developing better interventions for the relief of chronic pain, little is known about the mechanisms underlying this condition. However, transient receptor potential (TRP) ion channels in nociceptors have been shown to be essential players in the generation and progression of pain and have attracted the attention of several pharmaceutical companies as therapeutic targets. Unfortunately, TRP channel inhibitors have failed in clinical trials, at least in part due to their thermoregulatory function. Botulinum neurotoxins (BoNTs) have emerged as novel and safe pain therapeutics because of their regulation of exocytosis and pro-nociceptive neurotransmitters. However, it is becoming evident that BoNTs also regulate the expression and function of TRP channels, which may explain their analgesic effects. Here, we summarize the roles of TRP channels in pain, with a particular focus on TRPV1 and TRPA1, their regulation by BoNTs, and briefly discuss the use of BoNTs for the treatment of chronic pain.